IMPLEMENTATION OF GROUP SETTING REBT COUNSELING TO REDUCE THE CONSUMPTION OF ADOLESCENSE - Thaheransyah Thaheransyah; Anggi Fitria; Rosdialena Rosdialena; Sri Utami (IAIN Batusangkar, 2022)
The consumptive attitude is an unreasonable thought so that economically when it becomes an action it causes waste and cost inefficiency. Psychologically it causes anxiety and insecurity. Meanwhile, REBT Counseling is to improve and change the attitudes, perceptions, ways of thinking, beliefs and views of the counselee which are irrational to become rational, so that they can develop themselves and achieve optimal self-realization and also there is no module for changing consumptive attitudes among adolescents. The research method uses the experimental method. data collection techniques were interviews and questionnaires, interviews were conducted with two informants who participated in the family and questionnaires were given to adolescents so that they could provide information and contribute to the research conducted. The data analysis technique used is descriptive data analysis, namely by describing the application of REBT counseling with group settings to reduce consumptive attitudes. The results of the research conducted found that from the results of the pre-test 30 adolescents 1 (3.3%) were in the very high category, 10 people (33.3%) were in the high category, 12 (40%) were in the medium category, 6 people were in the high category. (20%) are in the low category and 1 person (3.3%) is in the very low category of consumptive attitudes.